Technology enhanced learning integration into organizations - Trepulė, Elena (Vytautas Magnus University, 2015)
The study presents a framework of responsible and responsive technology enhanced learning integration into organizations. Applying the theories of integration of innovation in an organization, technology enhanced learning integration criteria groups have been identified and validated in this study in the following sequence: 1) Strategy and management, 2) Information communication technologies and infrastructure, 3) Continuous professional staff development, 4) Technology enhanced learning curriculum, 5) Support systems, 6) Quality assurance, and 7) Marketing and business development. The implementation of framework of technology enhanced learning integration into three types of organizations - vocational education and training, business and community organizations- have been researched and results presented. The study aimed at presenting the complexity of TEL implementation in various organisations, searching for commonalities and researching separate organisational cases.